Kajian Kontribusi Penerapan Building Information Modeling (BIM) dalam Proyek BUMN Konstruksi pada Tahun 2022 - Noviani, Shanti Astri; Sarifah, Fitriana (Universitas Pendidikan Nasional, 2025)
Technological advances in the construction industry have produced a system known as Building Information Modeling (BIM). Before BIM, AutoCAD, SAP, and Ms. Project were widely used for project management. The use of this application takes longer because its components cannot be integrated into one system. This will have an impact on increasing costs and human resources required to complete the project if using the application compared to using BIM. BIM can represent all project work in digital form. The implementation of BIM has been widely used by state-owned construction companies in 2022, including PT Waskita Karya, PT Nindya Karya, PT Brantas Abipraya, PT Adhi Karya and PT Nindya Karya. This study uses a combination of qualitative and quantitative methods by collecting information obtained from the 2022 construction services annual report and quantifying the weight of the problem variables encountered. Based on the results of the study, it was found that the infrastructure development of each state-owned construction company is uneven and has advantages in their respective fields, such as dams, power plants, bridges, buildings, public facilities and roads.